2016
DOI: 10.1097/rli.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cystic Lesions by Spectral Mammography

Abstract: Discriminating cystic from solid lesions with spectral mammography demonstrates promising results with the potential to reduce mammographic recalls. It is estimated that for each missed cancer at least 625 cystic lesions would have been correctly identified and hence would not have been needed to be recalled. Our results justify undertaking a larger reader study to refine the algorithm and determine clinically relevant thresholds to allow safe classification of cystic lesions by spectral mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…The present measurements on fresh tumour tissue showed a smaller, although still significant, difference compared to cyst fluid in terms of and . Hence, discrimination of these two tissue types in clinical practice may be more challenging than previously believed, but is still possible as also evidenced by a clinical pilot study conducted by Erhard et al (2016). Despite the large spread, no solid samples fall within the shaded region of the cyst distribution ( Figure 2), but 15 malignant samples (56% of the total number) overlap with the cyst distribution in terms of (Figure 2, area below the dotted line), and these samples would therefore be challenging to distinguish from cyst fluid.…”
Section: Discrimination Between Tissue Typesmentioning
confidence: 99%
“…The present measurements on fresh tumour tissue showed a smaller, although still significant, difference compared to cyst fluid in terms of and . Hence, discrimination of these two tissue types in clinical practice may be more challenging than previously believed, but is still possible as also evidenced by a clinical pilot study conducted by Erhard et al (2016). Despite the large spread, no solid samples fall within the shaded region of the cyst distribution ( Figure 2), but 15 malignant samples (56% of the total number) overlap with the cyst distribution in terms of (Figure 2, area below the dotted line), and these samples would therefore be challenging to distinguish from cyst fluid.…”
Section: Discrimination Between Tissue Typesmentioning
confidence: 99%
“…Recent advances in spectral mammography based on energy-resolved photon-counting x-ray detectors provide unique advantages in measuring breast tissue properties without injection of a contrast agent. Previous studies have shown that breast imaging using a photon-counting detector can improve signal-to-noise ratio through energy weighting, [12][13][14][15] improve lesion conspicuity, 16 discriminate between solid and cystic masses using material decomposition algorithms, 17 and allow for accurate estimates of breast density. [18][19][20] Photon-counting detectors are able to count individual photons and sort them according to their energies with energy resolution of a few keV.…”
Section: Introductionmentioning
confidence: 99%
“…MI could be used alongside breast tomosynthesis as well as mammography, though the effects need to be investigated. Erhard et al investigated using spectral mammography to avoid recalls by distinguishing fluid-filled cysts from malignant lesions [24]. If all recalls of fluid-filled cysts could be avoided, the total decrease of recalls would be 20%, with less than one missed cancer per 625 correctly identified cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning recall rates, the prospective studies show an increase, while the retrospective studies generally show a decrease [1517, 1922]. Spectral mammography is another alternative, with a recent study demonstrating its ability to distinguish between cystic and solid lesions [24]. …”
Section: Introductionmentioning
confidence: 99%